A DECADE OF RESEARCH ON THE PSYCHOLOGY OF RELIGION AND COPING: Things we assumed and lessons we learned - I. Pargament, Kenneth; Abu Raiya, Hisham (Psyke & Logos, 2007)
Recently, the field of psychology has begun to display a growing interest in religious coping methods and their implications for health and well-being. Empirical studies have yielded an interesting picture of the relationship between religious coping and physical and mental health. In this paper, we review some of the foundational assumptions on which the theory of religion and coping rests. Then, we summarize recent advances in research in the area of religion and coping. We conclude by highlighting some of the exciting new directions for research in the psychology of religion and coping.